I'll show myself out ebook Essays on midlife and motherhood. - Klein, Jessi (2022)
An instant New York Times bestseller, I'll Show Myself Out is the eagerly anticipated second essay collection from Jessi Klein, author of the acclaimed debut You'll Grow Out of It. Longlisted for the PEN Diamonstein-Spielvogel Award for the Art of the Essay "Sometimes I think about how much bad news there is to tell my kid, the endlessly long, looping CVS receipt scroll of truly terrible things that have happened, and I want to get under the bed and never come out. How do we tell them about all this? Can we just play Billy Joel's We Didn't Start the Fire and then brace for questions? The first of which should be, how is this a song that played on the radio?" In New York Times bestselling author and Emmy Award-winning writer and producer Jessi Klein's second collection, she hilariously explodes the cultural myths and impossible expectations around motherhood and explore the humiliations, poignancies, and possibilities of midlife. In interconnected essays like "Listening to Beyoncé in the Parking Lot of Party City," "Your Husband Will Remarry Five Minutes After You Die," "Eulogy for My Feet," and "An Open Love Letter to Nate Berkus and Jeremiah Brent," Klein explores this stage of life in all its cruel ironies, joyous moments, and bittersweetness. Written with Klein's signature candor and humanity, I'll Show Myself Out is an incisive, moving, and often uproarious collection.